Halal management system in restaurant operation: identifying the motivational factors - Razali, Nor Ellyna; Ungku Zainal Abidin, Ungku Fatimah; Othman, Mohhidin; Mohamad, Siti Fatimah (Penerbit Universiti Teknologi MARA (UiTM) Malaysia, 2017)
Malaysia is known as one of the top Islamic tourism destinations especially among Muslim Middle East tourists. Various services and halal food offered serve as the main attractions. Although foodservice companies today are growing abundantly, the number of Halal certified restaurants is still limited. Hence, the factors that motivates restaurant in obtaining halal certification and implementing halal management system in the foodservice industries need to be explored. Using a qualitative approach, 15 semi-structured interviews were carried out with halal executives, managers or supervisors from halal certified restaurants. The recorded interviews were transcribed, translated and coded for analysis using Atlas.ti version 7 to identify themes and patterns in the data. The finding of this research shows the customer demand, marketing benefits, external support and pressure, top management commitment and product safety and quality are the motivation factors in implementing halal certificate. This study provides a recent view and knowledge on motivation for implementing halal management system in restaurant industries.